Photothermo-chemotherapy of cancer employing drug leakage-free gold nanoshells. (February 2016) - Wang, Lu; Yuan, Yuanyuan; Lin, Shudong; Huang, Jinsheng; Dai, Jian; Jiang, Qing; Cheng, Du; Shuai, Xintao
Abstract: Combined photothermo-chemotherapy is a new cancer treatment modality that improves therapeutic outcome by synergistic actions of two different means. A reduction and pH dual sensitive polymeric vesicle encapsulating doxorubicin (DOX) was prepared and then decorated with a gold layer using a modified method of in situ gold seed growth. By tuning the compactness of gold layer, the gold nanoshell may possess a desirable light absorption peak for tumor photothermal therapy using near-infrared (NIR) laser irradiation, a method featuring high tissue penetrability essential for in vivo applications. The NIR light energy was converted into heat, which killed cancer cells in the vicinity and induced the rupture of nanoshell to release DOX inside tumor. Therefore, a combined photothermo-chemotherapy of tumor can be achieved precisely at tumor site. In addition, DOX released in the thermochemotherapeutic mode effectively penetrated tumor tissue, which is meaningful considering the intrinsic low tissue penetrability of nanomedicines. In nude mice bearing human Bel-7402 hepatoma, the photothermo-chemotherapy using DOX-loaded gold nanoshell appeared advantageous over a chemotherapy or a photothermal therapy alone.